1996
DOI: 10.1038/bjc.1996.528
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p21 (WAF1/CIP1) protein in clinical thyroid tissues

Abstract: Summary p21 (WAF1/CIP1) protein expression in various thyroid tissues, including thyroid carcinoma, was studied by means of immunohistochemistry using anti-p21 monoclonal antibody. Normal follicles and hyperplasias rarely expressed p21, whereas immunohistochemically positive cells were also too rarely found in follicular adenomas to justify these cases being classified as positive. Twenty eight of the 93 carcinomas examined (30.1%), however, were positive for p21. Of the p21-positive cases, 80% of the undiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
2
17
3
Order By: Relevance
“…They could neither detect any relationship of p21 nuclear immunoreactivity with pathological findings such as histological type and depth of the tumor invasion. Ito et al [15]reported similar results for thyroid carcinoma. For small–cell lung carcinoma, Marchetti et al [5]reported no clinical significance of p21 overexpression.…”
Section: Discussionsupporting
confidence: 73%
“…They could neither detect any relationship of p21 nuclear immunoreactivity with pathological findings such as histological type and depth of the tumor invasion. Ito et al [15]reported similar results for thyroid carcinoma. For small–cell lung carcinoma, Marchetti et al [5]reported no clinical significance of p21 overexpression.…”
Section: Discussionsupporting
confidence: 73%
“…In normal follicular cells, p27 expression was observed at a high incidence, whereas the immunoreactivity of p57 and p21 was only occasionally observed (data not shown), which was not different from the findings in previous studies [16][17][18]. In follicular cells forming small follicles and infiltrating lymphocytes, p57 immunoreactivity was diffusely observed (fig.…”
Section: Resultscontrasting
confidence: 44%
“…In the present study, the lower p21/WAF1 expression was a significant predictor of poorer overall survival in the univariate survival analysis (47% vs 31% of 5-year survival rate, P = 0.012) but not of the recurrence-free survival in either univariate or multivariate survival analyses. This prognostic significance of p21/WAF1 expression has been reported in some neoplasias (Gomyo et al, 1997;Ito et al, 1997;Jiang et al, 1997;Ogawa et al, 1997;Wagasuki et al, 1997), whereas other authors have failed to establish any such prognostic value (Ito et al, 1996;Backe et al, 1997;Diab et al, 1997). The mechanisms by which the expression of p21/WAF1 is associated with better prognosis is not known in any detail as yet.…”
Section: Discussionmentioning
confidence: 86%